Lymphogranuloma venereum mimicking rectal cancer (T3 N2) and causing a rectovesical fistula. (August 2021) - Sadoghi, Birgit; Komericki, Peter; Igrec, Jasminka; Hutterer, Georg C; Wolf, Peter
We present the case of a 66-year-old bisexual patient suffering from painful bloody defecation, linked to rectal thickening, rectovesical fistula and enlarged lymph nodes in the mesorectal area. The patient was misdiagnosed with rectal cancer (T3 N2) on MRI but the symptoms of the patient were due to lymphogranuloma venereum. After adequate treatment with doxycycline, symptoms faded within days; a control MRI showed complete regression of all pathologic alterations.